MiR-146a-5p engineered hucMSC-derived extracellular vesicles attenuate Dermatophagoides farinae-induced allergic airway epithelial cell inflammation - Liu, Jiaxi; Xu, Zuyu; Yu, Jinyan; Zang, Xiao; Jiang, Shangde; Xu, Shuyue; Wang, Wei; Hong, Shanchao (Frontiers in Immunology, 2024)
Introduction Allergic asthma is prevalent in children, with Dermatophagoides farinae as a common indoor allergen. Current treatments for allergic airway inflammation are limited and carry risks. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) show promise as a cell-free therapeutic approach. However, the use of engineered MSC-EVs for D. farinae-induced allergic airway epithelial cell inflammation remains unexplored. Methods We generated miR-146a-5p-engineered EVs from human umbilical cord mesenchymal stem cells (hucMSCs) and established D. farinae-induced mouse and human bronchial epithelial cell allergic models. Levels of IL-1β, IL-18, IL-4, IL-5, IL-6, IL-10, IL-33, TNF-α and IgE were detected using ELISA. The relative TRAF6 and IRAK1 mRNA expression was quantified using qPCR assay and the NLRP3, NF-κB, IRAK1 and TRAF6 protein expression was determined using Western blotting. The regulatory effect of IRAK1 and TRAF6 by miR-146a-5p was examined using a dual luciferase reporter assay, and the nuclear translocation of NF-κB p65 into 16-HBE cells was evaluated using immunofluorescence assay. Results Treatment with hucMSC-EVs effectively reduced allergic inflammation, while miR-146a-5p engineered hucMSC-EVs showed greater efficacy. The enhanced efficacy in alleviating allergic airway inflammation was attributed to the downregulation of IRAK1 and TRAF6 expression, facilitated by miR-146a-5p. This downregulation subsequently led to a decrease in NF-κB nuclear translocation, which in turn resulted in reduced activation of the NLRP3 inflammasome and diminished production of inflammatory cytokines, including IL-6, TNF-α, IL-1β and IL-18. Conclusion Our study underscores the potential of miR-146a-5p engineered hucMSC-EVs as a cell-free therapeutic strategy for D. farinae-induced allergic airway inflammation, offering a promising avenue for boosting anti-inflammatory responses.